Optimization of Irrigation Requirements for the Markonahalli Command Area Using the SWAT Model - Archana K.; Suresh Ramaswwamy Reddy; Jagadish Vengala; Ashish Kumar Nayak (Journal of Engineering)
Irrigation requirements are instrumental in planning water distribution and reservoir management. The Markonahalli Dam is constructed across the Shimsha River and has a command area of 7000 ha in Kunigal Taluk of Tumkur District, Karnataka. It is a semiarid region that depends on canal irrigation from the reservoir. The Soil and Water Assessment Tool (SWAT) is employed to estimate potential evapotranspiration (PET) and crop evapotranspiration (ETc) for the command area. The model is calibrated and validated using evapotranspiration data from the Moderate Resolution Imaging Spectroradiometer (MODIS). The calibration and validation are performed using the Sequential Uncertainty Fitting-2 (SUFI-2) algorithm within the SWAT Calibration and Uncertainty Programs (SWAT-CUP). The results indicated reasonably good ETc estimations, with the coefficient of correlation (r) and Nash–Sutcliffe model efficiency (NSE) coefficient being 0.57 and 0.549 for calibration, and 0.165 and 0.105 for validation, respectively. The simulated ETc values are further used to calculate the gross irrigation requirement (GIR) for the command area. The irrigation requirement is further optimized for maximum crop yield using the Nondominated Sorting Genetic Algorithm II (NSGA-II) and Pareto curves. The optimization results show that 37.85% of the irrigation requirement can be conserved while maximizing crop yield.